Prevalence and risk factors for bovine tuberculosis in the State of Mato Grosso do Sul, Brazil - Israel Barbosa Guedes; Ilda Francisca Neves Bottene; Letícia Almeida Retumba Carneiro Monteiro; Jamil Manoel Leal Filho; Marcos Bryan Heinemann; Marcos Amaku; José Henrique Hildebrand Grisi-Filho; Ricardo Augusto Dias; Fernando Ferreira; Evelise Oliveira Telles; Vitor Salvador Picão Gonçalves; José Soares Ferreira Neto (Semina: Ciências Agrárias, 2016)
The objective of this study was to describe the epidemiological situation of bovine tuberculosis in Mato Grosso do Sul. The State was divided into three regions, Pantanal, Planalto Norte, and Planalto Sul. In each region, properties were randomly chosen and a pre-established number of animals were also randomly selected; these animals were submitted to the intradermal comparative cervical tuberculin diagnostic test. In total, 17,121 animals from 938 properties were tested. In cases of inconclusive results, the animals were retested with the same diagnostic procedure within a minimum interval of 60 days. An epidemiological questionnaire was administered in the properties sampled to investigate possible risk factors for the disease. In the State, the prevalence of infected herds was 1.3% (95% confidence interval [CI]: 0.72–2.37%) and that of infected animals was 0.035% (95% CI: 0.017–0.069%). Point estimates indicated a higher concentration of infected herds (2.61%; 95% CI: 1.31–5.15%) and infected animals (0.132%; 95% CI: 0.055–0.315%) in the Planalto Sul region, which has a predominance of dairy properties. The prevalence of herds infected with bovine tuberculosis was found to be associated with the production of milk, with technification in the mode of production represented by the use of mechanical milking. Thus, it is recommended that the State adopt strategies for the eradication of bovine tuberculosis, with the structuring of the surveillance system for detection and mitigation of infected herds, incorporating risk-based surveillance elements.